Defective support network: a major obstacle to coping for patients with heart failure: a qualitative study - Parvin Mangolian Shahrbabaki; Esmat Nouhi; Majid Kazemi; Fazlollah Ahmadi (Taylor & Francis Group, 2016)
Background: Heart failure as a chronic disease poses many challenges for a patient in his or her everyday life. Support in various aspects of life positively affects coping strategies and influences the well-being and health outcomes of heart failure patients. Inadequate support may lead to a worsening of symptoms, increased hospital readmissions, psychological disorders, and a reduced quality of life. Objective: This study explored obstacles to coping related to support for heart failure patients as viewed by the patients themselves and their family members and caregivers. Design: This qualitative study was conducted using content analysis. The 20 Iranian participants included 11 patients with heart failure, three cardiologists, three nurses, and three family members of heart failure patients selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the Lundman and Graneheim qualitative content analysis method. Results: During data analysis, 'defective support network' developed as the main theme along with four other categories of 'inadequate family performance', 'inadequate support by the healthcare team', 'distorted societal social support', and 'inadequate welfare support'. Conclusion: The findings of the current study can assist health authorities and planners in identifying the needs of patients with heart failure so as to focus and plan on facilitating their coping as much as possible by obviating the existing obstacles.